Positive electrode for lithium secondary battery and lithium secondary battery including the same

By using a base-treated MO6S8 additive in the positive electrode of lithium-sulfur batteries, the stability and reactivity of the electrode are enhanced, addressing polysulfide shuttling issues and improving battery performance.

JP7625711B2Active Publication Date: 2025-02-03LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023544571
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-20
Filing Date
2022-10-11
Publication Date
2025-02-03
Estimated Expiration
2042-10-11

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face issues with lithium polysulfide shuttling, leading to reduced capacity and life characteristics due to the dissolution of lithium polysulfide, which causes side reactions and decreases efficiency.

Method used

Incorporating a base-treated MO6S8 as an additive in the positive electrode active material layer to suppress lithium polysulfide migration, enhancing the stability and reactivity of the positive electrode.

Benefits of technology

The addition of MO6S8 improves discharge capacity, output characteristics, and life characteristics of lithium-sulfur batteries by stabilizing the positive electrode and reducing polysulfide shuttling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625711000001
    Figure 0007625711000001
  • Figure 0007625711000002
    Figure 0007625711000002
  • Figure 0007625711000003
    Figure 0007625711000003
Patent Text Reader

Abstract

The present invention relates to a positive electrode for a lithium secondary battery, which includes Mo6S8 that is treated with a base by an additive for a positive electrode active material layer, and a lithium secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0140210 dated October 20, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0003] The range of applications of lithium secondary batteries has expanded from portable electronic devices and communication devices to electric vehicles (EVs) and electric storage systems (ESSs), and there is an increasing demand for higher capacity lithium secondary batteries used as power sources for these devices.

[0004] Among the various lithium secondary batteries, the lithium-sulfur battery is a battery system that uses a sulfur-based material containing a sulfur-sulfur bond as the positive electrode active material and lithium metal, a carbon-based material in which lithium ions are inserted / deinserted, or silicon or tin that forms an alloy with lithium as the negative electrode active material.

[0005] In lithium-sulfur batteries, sulfur, the main positive electrode active material, has the advantages of being low weight per unit atom, abundant in resources, easy to supply and demand, inexpensive, non-toxic, and environmentally friendly.

[0006] In addition, lithium-sulfur batteries undergo a conversion reaction between lithium ions and sulfur at the positive electrode (S8+16Li + +16e ‐The theoretical discharge capacity of lithium-ion batteries (Li-FeS, Li-MnO2, Na-S) is 1,675mAh / g, and when lithium metal (theoretical capacity: 3,860mAh / g) is used in the negative electrode, it has a theoretical energy density of 2,600Wh / kg. This is a much higher value than the theoretical energy density of other battery systems currently being researched (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg) and lithium-ion batteries (250Wh / kg). Among the secondary batteries developed to date, lithium-ion batteries have attracted attention as high-capacity, environmentally friendly, and low-cost lithium secondary batteries, and much research is being conducted on next-generation battery systems.

[0007] During discharge, lithium-sulfur batteries undergo a reduction reaction in which sulfur accepts electrons at the positive electrode, and an oxidation reaction in which lithium is ionized at the negative electrode. During discharge of such lithium-sulfur batteries, lithium polysulfide (Li2S x , x=2~8) is generated, which is easily dissolved in the electrolyte and leaks out of the positive electrode, significantly reducing the reversible capacity of the positive electrode. The dissolved lithium polysulfide is also diffused to the negative electrode, causing various side reactions. In addition, such lithium polysulfide causes a shuttle reaction during the charging process, significantly reducing the charge / discharge efficiency.

[0008] Since the emergence of lithium polysulfide has a detrimental effect on the capacity and life characteristics of a battery, various techniques have been proposed to solve the problem of lithium polysulfide.

[0009] As an example, Korean Patent Publication No. 2017-0139761 discloses a positive electrode active material layer including a nitrogen-doped carbon material and a protective layer, and the positive electrode active material layer contains chitosan as a binder to delay the outflow of lithium polysulfide, thereby improving the capacity and life of the battery.

[0010] In addition, Korean Patent Publication No. 2016-0046775 discloses that a positive electrode coating layer made of an amphiphilic polymer is provided on a surface of a part of a positive electrode active part including a sulfur-carbon composite, thereby suppressing the outflow of lithium polysulfide and facilitating the movement of lithium ions, thereby improving the cycle characteristics of the battery.

[0011] In addition, Korean Patent Publication No. 2016-0037084 discloses that graphene coating on sulfur-containing carbon nanotube aggregates can block lithium polysulfide from dissolving out, thereby increasing the electrical conductivity and sulfur loading of the sulfur-carbon nanotube composite.

[0012] These patents have improved the performance or lifespan degradation problem of lithium-sulfur batteries to some extent by preventing the eruption of lithium polysulfide by introducing a material capable of adsorbing lithium polysulfide into the positive electrode in the form of an additive or coating layer, or by changing the material or structure of the positive electrode, but the effect is not sufficient. In addition, the newly introduced material may cause degradation problems, and the methods presented in these patents are not only somewhat complicated, but also have problems such as limitations on the amount of positive electrode active material that can be added (i.e., loading amount). Therefore, there is a need to develop a lithium-sulfur battery with excellent performance that solves the lithium polysulfide eruption problem. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Korean Patent Publication No. 2017-0139761 [Patent Document 2] Korean Patent Publication No. 2016-0046775 [Patent Document 3] Korean Patent Publication No. 2016-0037084 Summary of the Invention [Problem to be solved by the invention]

[0014] Here, the present inventors have conducted extensive research to solve the above problems, and have found that if base-treated Mo6S8 is added as an additive to a positive electrode active material layer of a positive electrode for a lithium secondary battery, the problem of lithium polysulfide generation occurring in a lithium secondary battery including the positive electrode, particularly a lithium-sulfur battery, can be solved, and the stability of the positive electrode active material layer can be improved, thereby reducing the overvoltage of the lithium-sulfur battery and improving the discharge capacity and output characteristics, thereby completing the present invention.

[0015] Therefore, an object of the present invention is to provide a positive electrode for a lithium secondary battery that can suppress the emergence of lithium polysulfides and improve the characteristics of a lithium-sulfur battery.

[0016] Another object of the present invention is to provide a lithium secondary battery including the positive electrode. [Means for solving the problem]

[0017] In order to achieve the above objective, The present invention includes a current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; The positive electrode active material layer includes a positive electrode active material and an additive, The additive provides a positive electrode for a lithium secondary battery comprising base-treated Mo6S8.

[0018] The present invention also provides a lithium secondary battery comprising the positive electrode of the present invention; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte. Effect of the Invention

[0019] The positive electrode for a lithium secondary battery according to the present invention contains base-treated Mo6S8 as an additive in the positive electrode active material layer, and thus has an excellent effect of suppressing the outflow of lithium polysulfide, thereby improving the stability of the positive electrode active material layer.

[0020] Therefore, the lithium secondary battery including the positive electrode for lithium secondary battery according to the present invention can exhibit the effects of reducing overvoltage and improving discharge capacity and output characteristics. [Brief description of the drawings]

[0021] [Figure 1] 1 is a graph showing an evaluation of the initial discharge capacity of the lithium-sulfur battery of Experimental Example 1. [Diagram 2] 1 is a graph showing the measured life characteristics of the lithium-sulfur battery of Experimental Example 1. [Diagram 3] 1 is a graph showing the measured output characteristics of the lithium-sulfur battery of Experimental Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will now be described in more detail.

[0023] The terms and words used in this specification and claims should not be construed in a limited manner based on their ordinary or dictionary meaning, but should be construed in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to explain his / her invention in the best possible way.

[0024] The terms used in the present invention are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In the present invention, the terms "include" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0025] As used herein, the term "polysulfide" means "polysulfide ion (S x 2‐ , x=8, 6, 4, 2)) and Lithium polysulfide (Li2S x or LiS x -, x=8, 6, 4, 2) is a concept that includes all of these.

[0026] Positive electrodes for lithium secondary batteries The present invention relates to a cathode active material layer comprising: a current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; The positive electrode active material layer includes a positive electrode active material and an additive, The additive relates to a positive electrode for a lithium secondary battery that includes base-treated Mo6S8.

[0027] The Mo6S8 is a compound that inhibits the emergence of lithium polysulfides, and is generally produced using copper sulfide (Cus), molybdenum (Mo) and molybdenum disulfide (MoS2).

[0028] Specifically, copper sulfide (Cus), molybdenum (Mo) and molybdenum disulfide (MoS2) are ball-milled, and then heated in an inert atmosphere of hydrogen (H2) at a temperature of 800 to 1200°C to produce Cu2Mo6S8. In order to remove copper from the Cu2Mo6S8 compound, the Cu2Mo6S8 compound is added to an acidic solution and stirred to finally obtain Mo6S8.

[0029] In the manufacturing process, an acidic solution is used to remove copper, which can cause Mo6S8 to exhibit acidity. If Mo6S8, which exhibits acidity, is used as an additive to the positive electrode active material layer, the positive electrode active material layer also exhibits acidity, which can cause the positive electrode to become unstable and its reactivity to decrease.

[0030] Therefore, in the present invention, the Mo6S8 is treated with a base to neutralize the acidic atmosphere, thereby improving the stability of the positive electrode active material layer and suppressing the emergence of lithium polysulfide.

[0031] The base treatment may be carried out by adding Mo6S8 to an aqueous base solution and stirring the solution. In this case, the base may be lithium hydroxide (LiOH) or potassium hydroxide (KOH), preferably lithium hydroxide. The base treatment of Mo6S8 does not depend on the concentration of the aqueous base solution, so the concentration of the aqueous base solution is not particularly limited, but preferably an excess concentration can be used. The stirring time is also not particularly limited, and stirring can be carried out for a time commonly used in the art.

[0032] If non-base-treated Mo6S8 is used as an additive, the pH of the positive electrode active material layer containing it is 1 to 4.

[0033] Therefore, the positive electrode active material layer including the base-treated Mo6S8 can have a pH of 7 to 9 by neutralizing the acidic atmosphere of Mo6S8 through the base treatment, thereby improving the stability of the positive electrode, and improving the discharge capacity and life characteristics of a lithium secondary battery, preferably a lithium-sulfur battery, including the same, and improving overvoltage.

[0034] The additive may be included in an amount of 1 to 10 wt%, preferably 3 to 7 wt%, based on 100 wt% of the total base solid content included in the positive electrode active material layer. If the additive is included in an amount of less than 1 wt%, the effect of suppressing the outflow of lithium polysulfide is insignificant and the above-mentioned effects cannot be achieved. Also, if the additive is included in an amount of more than 10 wt%, the proportion of the positive electrode active material is relatively reduced, which may reduce the battery capacity, so it is preferable to determine the appropriate content within the above range.

[0035] The positive electrode active material is elemental sulfur (S8), Li2S n (n ≥ 1, n is an integer), organic sulfur compounds and carbon-sulfur polymers [(C2S x ) n , 2.5≦x≦50, n≧2, where x and n are integers; and the sulfur may be inorganic sulfur.

[0036] The positive electrode active material may preferably be a sulfur-carbon composite.

[0037] The sulfur-carbon composite may comprise a porous carbon material and sulfur at least partially within the interior and exterior surfaces of the porous carbon material.

[0038] The sulfur-carbon composite includes a porous carbon material that not only provides a framework to which the sulfur can be uniformly and stably fixed, but also complements the low electrical conductivity of sulfur to facilitate an electrochemical reaction.

[0039] The porous carbon material may be generally prepared by carbonizing various carbon precursors. The porous carbon material may have pores inside, with the average pore diameter being in the range of 1 to 200 nm, and the porosity or void ratio being in the range of 10 to 90% of the total volume of the porous carbon material. If the average pore diameter is less than the range, the pore size is merely at the molecular level, making it impossible to impregnate sulfur, and conversely, if it exceeds the range, the mechanical strength of the porous carbon material is weakened, making it unsuitable for use in the manufacturing process of an electrode.

[0040] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk-like, and any shape commonly used in lithium secondary batteries may be used without limitation.

[0041] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto. Preferably, the porous carbon material may be carbon nanotubes.

[0042] In the sulfur-carbon composite according to the present invention, the sulfur is located at least in one of the inner and outer surfaces of the porous carbon material, and may be present in an area of ​​less than 100%, preferably 1 to 95%, and more preferably 40 to 96% of the entire inner and outer surfaces of the porous carbon material. When the sulfur is present in the inner and outer surfaces of the porous carbon material within the above range, the maximum effect can be exhibited in terms of the electron transfer area and wettability with the electrolyte. Specifically, the sulfur is thinly and uniformly impregnated in the inner and outer surfaces of the porous carbon material within the above range, so that the electron transfer contact area can be increased during charging and discharging. If the sulfur is located in the area of ​​100% of the entire inner and outer surfaces of the porous carbon material, the porous carbon material is completely covered with sulfur, which reduces the wettability and contactability with the electrolyte, and thus cannot transfer electrons and cannot participate in the electrochemical reaction.

[0043] The sulfur-carbon composite may contain 65 to 90 wt %, preferably 70 to 85 wt %, and more preferably 72 to 80 wt %, of the sulfur, based on 100 wt % of the sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite is relatively high, which increases the specific surface area and increases the content of the binder during the preparation of the positive electrode. This increase in the amount of binder used ultimately increases the surface resistance of the positive electrode and acts as an insulator that prevents electron passage, which can reduce the performance of the battery. On the other hand, if the sulfur content exceeds the above range, the sulfur that cannot be bonded to the porous carbon material may gather together or be re-sprouted on the surface of the porous carbon material, making it difficult for the sulfur to receive electrons and therefore unable to participate in the electrochemical reaction, resulting in a loss of battery capacity.

[0044] The method for producing the sulfur-carbon composite of the present invention is not particularly limited in the present invention, and may be a method commonly used in the art. For example, the sulfur and the porous carbon material may be simply mixed and then heat-treated to form a composite.

[0045] In addition to the above-mentioned composition, the positive electrode active material may further include one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, a sulfur compound of these elements, and an alloy of these elements with sulfur.

[0046] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, the IIIA group elements may include Al, Ga, In, or Tl, and the IVA group elements may include Ge, Sn, or Pb.

[0047] In the positive electrode for a lithium secondary battery according to the present invention, the positive electrode active material may be included in an amount of 50 to 95 wt%, preferably 70 to 95 wt%, and more preferably 85 to 95 wt%, based on 100 wt% of the total base solid content included in the positive electrode active material layer. If the content of the positive electrode active material is less than the above range, the electrochemical reaction of the electrode is difficult to fully exert, and conversely, if it exceeds the above range, there is a problem that the physical properties of the electrode described below are deteriorated.

[0048] The positive electrode active material layer of the positive electrode for a lithium secondary battery of the present invention may further include a conductive material for smoothly transferring electrons within the positive electrode, and a binder for better adhesion of the positive electrode active material to a current collector.

[0049] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material, and can be used without limitation as long as it has electrical conductivity.

[0050] For example, the conductive material may be carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, thermal black, or carbon black; carbon derivatives such as carbon nanotubes or fullerene; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.

[0051] The content of the conductive material may be 1 to 10 wt% based on 100 wt% of the total base solid content contained in the positive active material layer. If the content of the conductive material is less than this range, electron transfer between the positive active material and the current collector is not easy, resulting in a decrease in voltage and capacity. On the other hand, if the content exceeds this range, the proportion of the positive active material is relatively decreased, resulting in a decrease in the total energy (charge) of the battery, so it is preferable to determine the appropriate content within the above range.

[0052] The binder supports the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to enhance the adhesive strength therebetween, and any binder known in the industry may be used.

[0053] For example, the binder may be one or a mixture or copolymer of two or more selected from the group consisting of fluororesin-based binders including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0054] The content of the binder may be 1 to 10 wt % based on 100 wt % of the total base solid content included in the positive electrode active material layer. If the content of the binder is less than this range, the physical properties of the positive electrode may be deteriorated and the positive electrode active material and the conductive material may fall off, and if the content of the binder is more than this range, the ratio of the positive electrode active material and the conductive material in the positive electrode may relatively decrease, resulting in a decrease in battery capacity, so it is preferable to determine an appropriate content within the above range.

[0055] The positive electrode current collector is not particularly limited as long as it supports the positive electrode active material, does not cause a chemical change in the battery, and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, plastic carbon, copper or stainless steel surface-treated with carbon, nickel, silver, etc., aluminum-cadmium alloy, etc. may be used.

[0056] The positive electrode current collector may have fine projections and recesses on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.

[0057] In the present invention, the method for manufacturing the positive electrode for the lithium secondary battery is not particularly limited, and a method known to those skilled in the art or various methods modified therefrom may be used.

[0058] For example, the positive electrode for the lithium-sulfur battery may be manufactured by preparing a positive electrode slurry composition including the above-mentioned composition, and then coating the positive electrode current collector with the positive electrode slurry composition to form the positive electrode active material layer.

[0059] The positive electrode slurry composition includes the positive electrode active material and additives described above, and may further include a binder, a conductive material, and a solvent.

[0060] The solvent is one that can uniformly disperse the positive electrode active material and additives. As such a solvent, water is most preferred as an aqueous solvent, and the water may be distilled water or deionized water. However, the solvent is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water may be used. Examples of the lower alcohol include methanol, ethanol, propanol, isopropanol, and butanol, and these may be preferably mixed with water.

[0061] The content of the solvent may be at a level that allows easy coating, and the specific content varies depending on the coating method and device.

[0062] The positive electrode slurry composition may further include, as necessary, a substance commonly used in the relevant technical field for the purpose of improving its function, etc., such as a viscosity modifier, a fluidizing agent, a filler, etc.

[0063] The method of applying the positive electrode slurry composition is not particularly limited in the present invention, and may include, for example, methods such as doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be applied onto the positive electrode current collector by a pressing or lamination method after forming the positive electrode slurry on a separate substrate.

[0064] After the coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time level that allows the solvent to be sufficiently removed, and the conditions may vary depending on the type of solvent, so are not particularly limited in the present invention. Examples include drying with warm air, hot air, or low humidity air, vacuum drying, and drying by irradiation with (far) infrared rays and electron beams. The drying speed is usually adjusted so that the solvent can be removed as quickly as possible within a speed range that does not cause cracks in the positive electrode active material layer due to stress concentration or the positive electrode active material layer to peel off from the positive electrode current collector.

[0065] Furthermore, the density of the positive electrode active material in the positive electrode can be increased by pressing the current collector after drying, for example, by die pressing or roll pressing.

[0066] The positive electrode manufactured by the above-mentioned composition and manufacturing method, specifically, the porosity of the positive electrode active material layer may be 50 to 80%, preferably 60 to 75%. If the porosity of the positive electrode is less than 50%, the filling degree of the positive electrode slurry composition including the positive electrode active material, additive, conductive material and binder becomes too high, and sufficient electrolyte that can exhibit ionic conduction and / or electrical conduction between the positive electrode active material cannot be maintained, so that the output characteristics and cycle characteristics of the battery may be reduced, and the overvoltage and discharge capacity reduction of the battery may become severe. On the other hand, if the porosity of the positive electrode is too high, exceeding 80%, there is a problem that the physical and electrical connection with the current collector is reduced, the adhesive strength is reduced, and the reaction is difficult, and the high porosity may be filled with electrolyte, resulting in a decrease in the energy density of the battery, so it is appropriately adjusted within the above range.

[0067] Lithium secondary battery The present invention also relates to a lithium secondary battery comprising the above-mentioned positive electrode of the present invention; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

[0068] The lithium secondary battery of the present invention may preferably be a lithium-sulfur battery.

[0069] The negative electrode may include a negative electrode current collector and a negative electrode active material layer coated on one or both sides of the negative electrode current collector, or the negative electrode may be a lithium metal plate.

[0070] The negative electrode current collector is for supporting the negative electrode active material layer, and is the same as that described for the positive electrode current collector.

[0071] The negative active material layer may include a conductive material, a binder, etc. in addition to the negative active material. In this case, the conductive material and the binder are the same as those described above.

[0072] The negative electrode active material is a lithium ion (Li +The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.

[0073] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitride, or silicone. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0074] Preferably, the negative electrode active material is lithium metal, and specifically, may be in the form of a lithium metal thin film or lithium metal powder.

[0075] A separator may be interposed between the positive electrode and the negative electrode.

[0076] The separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transported between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material, and may be any material that is generally used as a separator in a lithium secondary battery without any particular limitations. Such a separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.

[0077] The separation membrane is preferably one that has low resistance to the ion migration of the electrolyte and has excellent moisture-absorbing capacity for the electrolyte.

[0078] The separator may be made of a porous substrate, and the porous substrate may be any porous substrate generally used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric or a polyolefin-based porous membrane made of high-melting-point glass fiber, polyethylene terephthalate fiber, or the like may be used, but is not limited thereto.

[0079] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate generally used in electrochemical devices may be used. For example, the porous substrate may be a polyolefin such as polyethylene or polypropylene, a polyester such as polyethyleneterephthalate or polybutyleneterephthalate, a polyamide, a polyacetal, a polycarbonate, a polyimide, a polyetheretherketone, a polyethersulfone, a polyphenyleneoxide, a polyphenylenesulfide, a polyethylenenaphthalate, a polytetrafluoroethylene, a polyvinylidene fluoride, a polyvinyl chloride, or the like. The material may include one or more materials selected from the group consisting of poly(p-phenylene benzobisoxazole), polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylate.

[0080] The thickness of the porous substrate is not particularly limited, and may be 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but if the thickness is smaller than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.

[0081] The average diameter and porosity of the pores in the porous substrate are not particularly limited, but may be 0.001 to 50 μm and 10 to 95%, respectively.

[0082] The electrolyte contains lithium ions and serves to cause an electrochemical oxidation or reduction reaction between the positive electrode and the negative electrode through the lithium ions.

[0083] The electrolyte may be a non-aqueous electrolyte solution or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte that includes an electrolyte salt and an organic solvent.

[0084] The electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt may be any salt commonly used in electrolytes for lithium secondary batteries. For example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl ‐4 , CH3SO3Li, (CF3SO2)2NLi, LiN(SO2F)2, lithium chloroborane, lithium lower aliphatic carboxylates, lithium 4-phenylborate, lithium imide, etc. can be used.

[0085] The concentration of the lithium salt may be 0.2 to 2 M, specifically 0.4 to 2 M, more specifically 0.4 to 1.7 M, depending on various factors such as the exact composition of the electrolyte solvent mixture, the solubility of the salt, the conductivity of the dissolved salt, the charge and discharge conditions of the battery, the operating temperature, and other factors known in the lithium battery field. If the lithium salt is used at a concentration less than 0.2 M, the electrolyte conductivity may be reduced, resulting in a decrease in electrolyte performance, and if the concentration exceeds 2 M, the viscosity of the electrolyte may increase, resulting in a decrease in lithium ion mobility.

[0086] The organic solvent contained in the non-aqueous electrolyte may be any organic solvent commonly used in electrolytes for lithium secondary batteries, and may be, for example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc., which may be used alone or in combination of two or more thereof, and among these, representative examples include ether-based compounds.

[0087] The ether-based compound may include acyclic ethers and cyclic ethers.

[0088] For example, the acyclic ether may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, but is not limited thereto.

[0089] As an example, the cyclic ether may be one or more selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, and isosorbide dimethyl ether, but is not limited thereto.

[0090] Among the organic solvents, the ester may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, or a mixture of two or more of these, but is not limited thereto.

[0091] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.

[0092] Specific examples of the cyclic carbonate compound include any one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or a mixture of two or more of these. Examples of halides thereof include, but are not limited to, fluoroethylene carbonate (FEC).

[0093] The electrolyte may further include a nitric acid or nitrite-based compound as an additive in addition to the electrolyte salt and the organic solvent. The nitric acid or nitrite-based compound forms a stable coating on the lithium metal electrode, which is the negative electrode, to improve charge / discharge efficiency.

[0094] The nitric acid or nitrite compound is not particularly limited in the present invention, but may be one selected from the group consisting of inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), and ammonium nitrite (NH4NO2); organic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrate, propyl nitrate, butyl nitrate, pentyl nitrate, and octyl nitrate; and organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, and dinitrotoluene, and combinations thereof. Preferably, lithium nitrate is used.

[0095] The electrolyte injection may be performed at an appropriate stage during the manufacturing process of the electrochemical device depending on the manufacturing process and required properties of the final product, i.e., before assembly of the electrochemical device or at the final stage of assembly of the electrochemical device.

[0096] The lithium secondary battery according to the present invention can be manufactured by lamination (stack) and folding processes of the separator and the electrodes in addition to the general winding process.

[0097] The shape of the lithium secondary battery is not particularly limited, and may be various shapes such as a cylindrical shape, a laminated shape, a coin shape, and the like.

[0098] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. It is natural that such changes and modifications fall within the scope of the appended claims.

[0099] [Production Example 1. Production of LiOH-treated Mo6S8] 4.8g of CuS, 7.2g of Mo, and 12g of MoS2 were ball milled at 240 rpm for 16 hours. Then, it was heated in a furnace in a H2 / Ar atmosphere at 1000°C for 12 hours to produce Cu2Mo6S8. The Cu2Mo6S8 was added to an 8M aqueous hydrochloric acid solution and stirred at 50°C to produce Mo6S8 from which copper had been removed.

[0100] The Mo6S8 was added to a 0.1M LiOH aqueous solution and stirred for 24 hours to prepare LiOH-treated Mo6S8.

[0101] [Production example 2.Mo6S8 production] 4.8g of CuS, 7.2g of Mo, and 12g of MoS2 were ball milled at 240 rpm for 16 hours. Then, it was heated in a furnace in a H2 / Ar atmosphere at 1000°C for 12 hours to produce Cu2Mo6S8. The Cu2Mo6S8 was added to an 8M aqueous hydrochloric acid solution and stirred at 50°C to produce Mo6S8 from which copper had been removed.

[0102] <Manufacturing lithium-sulfur batteries> Example 1. A mixture was obtained by mixing the positive electrode active material, additive, thickener, and binder in a weight ratio of 91:5:1.5:2.5. The positive electrode active material was an S / CNT composite (S:CNT=75:25) obtained by mixing sulfur (a product of Sigma-Aldrich) with carbon nanotubes using a ball mill and then heat-treating at 155°C. The additive was the LiOH-treated Mo6S8 prepared in Preparation Example 1, the thickener was lithium-carboxymethylcellulose (Li-CMC, LiCMC1000, Dielchem), and the binder was styrene-butadiene rubber (SBR).

[0103] The mixture was mixed with water to prepare a positive electrode slurry composition for a lithium-sulfur battery.

[0104] The positive electrode slurry composition was coated on one side of a positive electrode current collector made of aluminum foil having a thickness of 20 μm, and then dried at 50° C. for 2 hours and rolled to prepare a positive electrode having a positive electrode active material layer.

[0105] The positive and negative electrodes were placed facing each other, a polyethylene separator having a thickness of 20 μm and a porosity of 45% was interposed therebetween, and 130 μl of electrolyte was then injected to prepare a lithium-sulfur battery.

[0106] In this case, a 40 μm-thick lithium metal thin film was used as the negative electrode, and a mixture of 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % lithium nitrate (LiNO3) dissolved in an organic solvent consisting of 1,3-dioxolane and dimethoxyethane (DOL:DME = 1:1 (volume ratio)) was used as the electrolyte.

[0107] Comparative Example 1 A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that vapor grown carbon fiber (VGCF) was used as an additive to the positive electrode slurry composition.

[0108] Comparative Example 2 A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the Mo6S8 prepared in Preparation Example 2 was used as an additive for the positive electrode slurry composition.

[0109] Experimental example 1. Characterization of lithium-sulfur batteries (1) Initial discharge capacity measurement The lithium-sulfur batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 were tested for charge / discharge characteristic changes using a charge / discharge measuring device (LAND CT-2001A, manufactured by Wuhan Co., Ltd.). The initial discharge capacity of the obtained batteries was measured under a charge / discharge condition of 0.1C / 0.1C, and the results are shown in FIG.

[0110] 1, the lithium-sulfur battery of Example 1 of the present invention exhibited an initial discharge capacity similar to those of Comparative Examples 1 and 2. However, it was confirmed that the lithium-sulfur battery of Example 1 of the present invention had an improved overvoltage compared to Comparative Examples 1 and 2.

[0111] (2) Life characteristics measurement The lithium-sulfur batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 were charged / discharged at 0.1C / 0.1C for the first 3 cycles, then charged / discharged at 0.2C / 0.2C for the next 3 cycles, and then charged / discharged at 0.3C / 0.5C for 60 cycles using a charge / discharge measuring device (LAND CT-2001A, manufactured by Wuhan Co., Ltd.) to measure the life characteristics, and the results are shown in FIG. 2.

[0112] 2, the lithium-sulfur battery of Example 1 of the present invention exhibited excellent life characteristics compared to Comparative Examples 1 and 2. Specifically, the lithium-sulfur battery of Example 1 showed a decrease in discharge capacity after 50 cycles, while Comparative Example 1 showed a gradual decrease in discharge capacity from 30 cycles and Comparative Example 2 showed a gradual decrease in discharge capacity from the beginning of cycles.

[0113] (3) Output characteristic measurement The lithium-sulfur batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to a HPPC test in which a discharge current of 0.5C was applied for 10 seconds at every 10% SOC in a fully charged state, and the resistance was measured. The results are shown in FIG. 3.

[0114] As shown in FIG. 3, the lithium-sulfur battery of Example 1 of the present invention has significantly improved resistance characteristics compared to Comparative Examples 1 and 2, and as a result, the output characteristics are improved, especially at SOC 40 or less.

[0115] As a result, it was confirmed that a lithium secondary battery, preferably a lithium-sulfur battery, including a positive electrode containing base-treated Mo6S8 as an additive can promote the switching between sulfur (S) and lithium sulfide (Li2S), thereby suppressing the eruption of lithium polysulfide, and increasing the stability of the positive electrode active material layer, thereby improving the overvoltage of the lithium-sulfur battery and improving its life and output characteristics.

Claims

1. a current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; The positive electrode active material layer includes a positive electrode active material and an additive, The additive is a base-treated Mo 6 S 8 Including, The pH of the positive electrode active material layer is 7 to 9, The positive electrode active material includes at least one selected from the group consisting of elemental sulfur (S8), Li2Sn (n≧1, n is an integer), an organic sulfur compound, and a carbon-sulfur polymer [(C2Sx)n, 2.5≦x≦50, n≧2, x and n are integers].

2. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the base for the base treatment includes lithium hydroxide or potassium hydroxide.

3. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the additive is included in an amount of 1 to 10 wt % based on 100 wt % of the total base solid content included in the positive electrode active material layer.

4. The positive electrode for a lithium secondary battery according to claim 1 , wherein the positive electrode active material comprises a sulfur-carbon composite.

5. The positive electrode for a lithium secondary battery according to claim 1 , wherein the positive electrode active material layer further comprises a binder or a conductive material.

6. A lithium secondary battery comprising: the positive electrode according to claim 1 ; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

7. 7. The lithium secondary battery according to claim 6, wherein the lithium secondary battery is a lithium-sulfur battery.

Citation Information

Patent Citations

  • Electrode material and its manufacture

    JP1991194851A

  • Primer-coated cathode current collector and magnesium secondary battery equipped therewith

    JP2013533601A

  • Electrochemical magnesium cell and method for preparing the same

    JP2015513381A

  • KR2016‐0037084

  • KR2016‐0046775